2015
DOI: 10.1371/journal.pone.0123746
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Access to Services in Rural Emergency Departments of Quebec and Ontario

Abstract: IntroductionRural emergency departments (EDs) are important safety nets for the 20% of Canadians who live there. A serious problem in access to health care services in these regions has emerged. However, there are considerable geographic disparities in access to trauma center in Canada. The main objective of this project was to compare access to local 24/7 support services in rural EDs in Quebec and Ontario as well as distances to Levels 1 and 2 trauma centers.Materials and MethodsRural EDs were identified thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 26 publications
0
41
0
1
Order By: Relevance
“…[48][49][50] Existing Canadian and American studies evaluating inequality in health care based on geographic variation identified factors contributing to such variation including patient need, patient preferences, illness burden, insurance coverage and community wealth/poverty. [51][52][53][54][55] Further research is required into possible medical practice and health system barriers, such as referral wait times, misdiagnoses, geographic distance to clinic and urbanity that may result in longer times to diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50] Existing Canadian and American studies evaluating inequality in health care based on geographic variation identified factors contributing to such variation including patient need, patient preferences, illness burden, insurance coverage and community wealth/poverty. [51][52][53][54][55] Further research is required into possible medical practice and health system barriers, such as referral wait times, misdiagnoses, geographic distance to clinic and urbanity that may result in longer times to diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Catchment areas can also delineate locations that are ostensibly served by a service facility. This type of information can help determine whether at-risk populations are getting access to health care [31], if patients with mental health issues can get adequate access to specialized doctors, or determine whether there is a differential stress on some services due to higher catchment flows in some others compared to others [32]. Upon inspection, the demand/supply ratios for the catchment areas provide insight into where resources need to be reallocated or where personnel need to be re-assign to better meet the demands of the population in the service area [33].…”
Section: Catchment Areasmentioning
confidence: 99%
“…Cost-cutting by provincial governments in the early to mid-1990s in response to growing levels of public debt and economic slowdown led to the closure of a number of smaller hospitals in rural and remote areas. This was accompanied by the introduction of geographically based regional health authorities in most provinces and a Health Services Restructuring Commission in Ontario which in turn accelerated the tendency to concentrate hospital and emergency department resources in larger hospitals outside of sparsely populated rural and remote communities [13,14]. After these changes were introduced, 22.5% of Canadian live more than one hour driving distance by road from either a level I or level II trauma centre [13].…”
Section: Canadamentioning
confidence: 99%